Transformation of Guided Democracy Narratives in History Textbooks from Curriculum 2013 to Merdeka Curriculum: A Wodakian Analysis - Yuda Ariwinata; Aisiah Aisiah (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This study examines the transformation of Guided Democracy narratives in Indonesian senior high school history textbooks following the shift from the 2013 Curriculum (Revised 2018 Edition) to the Merdeka Curriculum. Employing Ruth Wodak’s Discourse-Historical Approach (DHA), the research analyzes how political memory, executive authority, and democratic legitimacy are discursively constructed and recontextualized across curricular frameworks. The data consist of official Grade XII history textbooks published by the Ministry of Education under both curricula. Through qualitative critical discourse analysis, this study identifies shifts in framing strategies, lexical choices, argumentation patterns, and representations of institutional balance. The findings reveal that the 2013 Curriculum predominantly utilizes crisis-based legitimation, portraying parliamentary instability as justification for executive centralization and emphasizing national stability and unity. In contrast, the Merdeka Curriculum presents a more structural and contextual interpretation, highlighting institutional consequences, democratic trade-offs, and the complexity of political power relations. This shift indicates a movement from integrative-legitimative historiography toward a more reflective and dialogic historical representation. The study contributes theoretically by demonstrating that curriculum reform functions as a mechanism of ideological rearticulation within educational discourse. It also highlights the role of textbooks as strategic sites for negotiating national identity and democratic consciousness. Ultimately, the transformation of Guided Democracy narratives illustrates how curricular change reshapes students’ historical awareness and civic orientation in contemporary Indonesia.